Does Adjunctive Tigecycline Improve Outcomes in Severe-Complicated, Nonoperative Clostridium difficile Infection?. (10th February 2017) - LaSalvia, Mary T.; Branch-Elliman, Westyn; Snyder, Graham M.; Mahoney, Monica V.; Alonso, Carolyn D.; Gold, Howard S.; Wright, Sharon B.
Abstract: Severe Clostridium difficile infection is associated with a high rate of mortality; however, the optimal treatment for severe- complicated infection remains uncertain for patients who are not candidates for surgical intervention. Thus, we sought to evaluate the benefit of adjunctive tigecycline in this patient population using a retrospective cohort adjusted for propensity to receive tigecycline. We found that patients who received tigecycline had similar outcomes to those who did not, although the small sample size limited power to adjust for comorbidities and severity of illness.